Cardenolide and glucosinolate accumulation in shoot cultures of Erysimum crepidifolium Rchb. - Horn, Elisa; Kemmler, Yvonne; Kreis, Wolfgang; Munkert, Jennifer (In Vitro Cellular & Developmental Biology-Plant, 2020)
Erysimum crepidifolium Rchb. is one of the few Brassicaceae species accumulating glucosinolates as well as cardenolides. This is possibly providing a selective advantage in evolution as both compounds are part of a chemical defense system. In order to study the biosynthesis of these compounds, a regeneration protocol for E. crepidifolium using in vitro shoot cultures derived from seeds has been developed. Murashige and Skoog (MS) culture medium supplemented with various combinations of cytokinins and auxins was used. MS medium containing NAA (naphthaleneacetic acid, 0.04 mg mL−1) and BAP (6-benzylaminopurine, 0.2·10−2 mg mL−1) proved to be optimal for root formation. Plantlets developed well on modified MS medium without the use of phytohormones. About 80% of the plantlets rooted in vitro developed into intact plants after transfer to the greenhouse. Cardenolides (1.75 mg g−1 dry weight (DW)) were detected in cultured shoots on solid DDV media while glucosinolates mainly accumulated in roots where 0.025 mg g−1 FW were detected in shoots cultured on the same medium (DDV). The expression of two progesterone 5β-reductase and three Δ5-3β-hydroxysteroid dehydrogenase genes were measured in shoot cultures since the encoded enzymes are supposed to be involved in cardenolide biosynthesis. E. crepidifolium shoot cultures propagated on solid media meet the necessary requirements, i.e., clonal homogeneity, product accumulation, and gene expression, for a suitable model to study cardenolide but not glucosinolate biosynthesi